Study of Variations in CPO Olein Fractionation Methods on the Yield and Quality of Red Palm Oil - Edy Wibowo Kurniawan; Rahmadi; Muh Yamin; Andi Lisnawati; Bangun P Nusantoro; mujibu Rahman; Farida Aryani (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2024)
Red palm oil is a palm oil derivative product, where refining is simple without a bleaching process, so it has good nutritional content (carotenoids or as pro-vitamin A, vitamin E, tocopherols and tocotrienols), and also provides health benefits. However, there is no information on processing red palm oil by choosing a better separation method to produce red oil with maximum yield but still good quality. This research was carried out using 2 separation methods, namely centrifugation and sedimentation. The treatments consisted of different temperatures used during the process of homogenizing CPO (3 temperature variations), including P1 = 80℃, P2 = 70℃ P3 = 60℃. This research used a CRD. From the results of the studies, it was concluded that difference in fractionation method and temperature indeed had some effects on the yield and quality of red palm oil. Furthermore, the best yield results during the study were obtained by centrifugation at 80°C temperature The yield was 69% and the quality characteristics were free fatty acid content of 2.78%, water content of 1.61%, DOBI value of 2.03, and beta-carotene content of 423.05 ppm.